Conditions for apprentices' learning activities at work - Messmann, Gerhard [Verfasser]; Mulder, Regina H. [Verfasser] (My University, 2015)
"The aim of this study was to investigate how apprentices' learning activities at work can be fostered. This is a crucial issue as learning at work enhances apprentices' competence development and prepares them for professional development on the job. Therefore, we conducted a study with 70 apprentices in the German dual system and examined the role of school-work alignment and work characteristics as facilitators of apprentices' work-based learning activities. Outcomes of path modelling showed that apprentices' engagement in enquiring was facilitated by their perception of work orientation at school. Likewise, if apprentices perceived work as complex and providing autonomy and needs support, they more strongly reflected individually on work-related challenges. Finally, as a consequence of perceiving their work as complex, they sought reflective interactions with others. The study, thus, highlights the importance of challenging, empowering and supportive work environments and of alignment between school and work as facilitators of apprentices' learning activities at work." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 2 Lehr-Lerngestaltung; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Kompetenzentwicklung; Lernumgebung